Integrating data from cold-water coral habitats increase knowledge on age and growth studies: the case of Helicolenus dactylopterus (Delaroche, 1809) in the central Mediterranean - Sion, Letizia; Cornacchia, Laura; Galasso, Gabriele; D’Onghia, Gianfranco; Carbonara, Pierluigi (Frontiers in Marine Science, 2024)
The aim of this study is to provide new insights on the age and growth of H. dactylopterus in the north-western Ionian Sea (central Mediterranean) by using different data sets and comparing three different methods, one direct by otolith reading corroborated by two indirect methods, by means of back calculation and Length Frequency Distribution analysis (LFDa), in order to obtain robust data for use in analytical management models. A total of 1403 specimens of blackbelly rosefish were sampled from habitats explored on muddy bottoms in the depth range 106-721 m and 309 individuals caught in the cold-water coral habitat between 418 and 635 m in depth. The length-frequency distributions of blackbelly rosefish showed a polymodal pattern in both habitats explored, with medium-small individuals caught on muddy bottoms and larger ones in coral habitats and canyons. The maximum age observed in females was 13 years (315 mm TL), while in males it was 15 years (336 mm TL), and no significant difference was observed comparing age-length keys from otolith readings of females with the males. The analysis of the daily increments allowed us to validate the average length of the first year of age (approximately 90-100 mm LT) obtained from the three different methods used. No significant difference was highlighted comparing the average lengths of age class 1, calculated with the direct method and by counting the daily increments. The von Bertalanffy growth parameters were estimated for the sexes and for the whole population from otolith readings and for the entire population by LFD analysis and the back calculation method. The growth curves were comparable between the different methods and no significant difference was observed. The von Bertalanffy growth parameters estimated for the different methods were comparable (otolith readings L∞ 494 mm, k=0.06 years-1, t0=-3.00 years; back calculation method L∞ 487 mm, k=0.06 years-1, t0=-2.30 years; LFDa L∞ 415 mm, k=0.07 years-1, t0=-2.23 years), indicating a slow growth in accordance with what has already been observed in other areas of the Mediterranean.